ANALISIS PENGARUH INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PERBANKAN DI INDONESIA - YUSKAR .; DHIA NOVITA (Program Studi Magister Manajemen FE Unsri, 2014)
This study aims to analyze and examine the effectof intellectual capitalon firm value through financial performance as an intervening variable. The value of the company as the dependent variable was measured using a Price to Book Value (PBV), the financial performance as measured by proxy intervening variavel return on equity (ROE) andearnings per share (EPS). While intellectual capital is measured using value added intelctual capitalco efficient (VAICTM),which consists of three components: human capital, organizational capital, and relational or customer capital. The objectof the research is the entire banking companies listed in Indonesia Stock Exchange (IDX) according to defined criteria. Thenumber of samples that meet the criteria of only 29 banks with the financial reporting period from 2010 to2013. Based on the analysis and hypothesis testing, this study showed the following results: (a) Intellectual capital has an influence on the financial performance proxied by return on equity (ROE) and earnings per share(EPS), (b) the financial performance proxied by ROE and EPS positive effecton firm value(PBV), (c) Intellectual capital has no direct influenceon the value ofthe company, and(d) Intellectual capital effectindi rectlyon firm value(PBV) throughfinancial performancereturn on equity(ROE) andearnings per share(EPS). It explains that, intellectual capital owned perusahaan, which include; human capital, organizational capital and relational capital or integrated customer will result inbetter financial performance, will further enhance the company's overall value.